Pattern and predictors of help-seeking behaviour among women exposed to violence in Tanzania (Tanzania Medical Journal, 2021)
BackgroundThere is limited research evidence on the pattern and factors influencing help-seeking among women experiencing intimate partner violence (IPV) in sub-Saharan Africa and in Tanzania in particular. This study sought to assess the pattern and predictors of help-seeking among women reporting ever experienced violence in Tanzania.MethodsThis was analysis of secondary data of the 2015-2016, Tanzania Demographic and Health Survey and Malaria Indicator Survey (TDHS – MIS). Out of 13,266 eligible women, for 9,322 (70.3%) women were analyzed using STATA. The findings were summarized using descriptive statistics – frequencies and percentages. The association between the dependent variable (help-seeking behavior) and independent variables was established using Pearson’s Chi Square test and Chi square test for trend; and associations with p-value <0.05 were considered statistically significant. Additionally, the Poisson regression model was used to determine independent predictors associated with the dependent variable.Results Overall, 4060 (43.6%) women reported ever experienced physical, sexual, or emotional violence. Of these, 2196 (54.1%) [95% CI=52.5, 55.6] reported seeking help in response. The victims of violence mentioned preferred several sources where they sought help. These include consanguine relative, husband’s or partner’s relatives. Independent factors associated with help-seeking include advanced age and not being in marital union (p< 0.001).Conclusion Combating violence may require addressing factors that impair help-seeking by the victims. Young women and those in union (married or cohabiting) need be particularly supported to seek help in rponse to violence. Factors that contribute to the culture of silence in these groups such as lack of assertiveness and self-confidence among young women and socioeconomic dependence and cultural inhibitions among married or cohabiting women need to be recognized and addressed accordingly.